To the reader - Yulia A. Zubok; Nina A. Seliverstova (Наука. Культура. Общество, 2023)
The editors present a thematic issue of the journal dedicated to Vladimir Ilyich Chuprov, whose 85th birthday would have taken place on August 8. The emphasis is on the fact that the issue is conceived not only as a tribute to the scientist, but also as a continuation of his ideas and designs.